ecrã|screen|inter|face. da imagem-mapa à imagem-libido. from the image-map to the image-libido - Loureiro, Luis M. (2014)
The screen has become a constituent of the kinetic visual regime of modernity that is constantly producing an inter|face|world whose presence manifests itself as a totality in the quotidian horizon of events. On one hand, its mediation allows us an immediate access to the speed, laterality and superficiality of images permitting their accelerated movement to a gaze that processes them as shareable images-map: coded images whose decoding assure the immediate subjective recognition and orientation in the world he navigates. However this (auto)mobilization guaranteed by the sociotechnical screen, one of a telepresence, becomes also a paradoxical extatic (i)mobilization. In an inter|face|world one can no longer define clear separations. There are no borders such as subject/object or private/public. From new readings of Lacan (Perniola, 2006; Žižek, 2009; Nusselder, 2009), we also propose the concept of an image-libido that will allow us to describe the subjective immersion in a symbiotic inter|face. We’re now dealing with the libidinal power of an intimate non-shareable image that transforms us into desiring statue-men (Loureiro, 2007), hybrids of a never fulfilled identification.